A Facile, Chemoselective and Eco-friendly Solid Phase Synthesis of Enaminones Catalyzed by L-Proline - S. Bhupathi, Raja; Rama Devi, B.; Dubey, P.K. (Asian Journal of Chemistry, 2011)
A facile and chemoselective method for the synthesis of enaminones by the reaction of aromatic primary amines with various β-ketoesters in the presence of L-proline as activator under solid phase is described. The reactions are promoted by the catalyst in short time (5-6 min) under ambient conditions, without any side products.